Pengalaman Regulasi Emosi dalam menghadapi Romantic Jealousy pada Dewasa Awal yang sedang Berpacaran [Emotion Regulation Experiences in Coping with Romantic Jealousy among Dating Emerging Adults] - Elviana Rizky Maharani; Zerlinda Christine Aldira Sanam; Diana Aipipidely (Indonesia Berdaya, 2026)
Romantic jealousy is an emotional response that arises when individuals perceive a threat to their romantic relationship. The experience of jealousy involves not only emotional reactions but also cognitive processes, behavioral responses, and the ways individuals regulate their emotions. This study aimed to explore emotion regulation experiences in coping with romantic jealousy among emerging adults who are involved in romantic relationships. A qualitative approach with a descriptive design was employed. The participants consisted of eight university students in emerging adulthood who had experienced jealousy in a romantic relationship. Data were collected through semi-structured interviews and analyzed using Thematic Analysis. The findings revealed four major themes: triggers of jealousy, the dynamics of romantic jealousy, emotion regulation strategies, and changes in emotion regulation. The results indicate that romantic jealousy generates various cognitive, emotional, and behavioral responses and may also contribute to changes in individuals’ emotion regulation abilities over time. These findings provide a deeper understanding of how emerging adults experience and manage romantic jealousy within the context of romantic relationships.   Abstrak. Kecemburuan romantis (romantic jealousy) merupakan respons emosional yang muncul ketika individu mempersepsikan adanya ancaman terhadap hubungan romantis yang dimiliki. Pengalaman kecemburuan tidak hanya melibatkan aspek emosional, tetapi juga proses kognitif, perilaku, serta cara individu meregulasi emosi yang muncul. Penelitian ini bertujuan untuk mengeksplorasi pengalaman regulasi emosi dalam menghadapi romantic jealousy pada dewasa awal yang sedang menjalani hubungan romantis.  Penelitian ini menggunakan pendekatan kualitatif dengan desain deskriptif. Partisipan penelitian berjumlah 8 orang mahasiswa dewasa awal yang pernah mengalami kecemburuan dalam hubungan romantis. Data dikumpulkan melalui wawancara semi-terstruktur dan dianalisis menggunakan Analisis Tematik. Hasil penelitian menunjukkan empat tema utama, yaitu pemicu kecemburuan, dinamika romantic jealousy, strategi regulasi emosi, dan perubahan regulasi emosi. Hal ini menunjukkan bahwa romantic jealousy tidak hanya memunculkan berbagai respons kognitif, emosional, dan perilaku, tetapi juga dapat diikuti oleh perubahan kemampuan regulasi emosi pada individu.